2020
DOI: 10.1038/s41533-020-00201-z
|View full text |Cite|
|
Sign up to set email alerts
|

Implementing a context-driven awareness programme addressing household air pollution and tobacco: a FRESH AIR study

Abstract: Most patients with chronic respiratory disease live in low-resource settings, where evidence is scarcest. In Kyrgyzstan and Vietnam, we studied the implementation of a Ugandan programme empowering communities to take action against biomass and tobacco smoke. Together with local stakeholders, we co-created a train-the-trainer implementation design and integrated the programme into existing local health infrastructures. Feasibility and acceptability, evaluated by the modified Conceptual Framework for Implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…Our study findings were translated directly into practical leverage points in the implementation strategies of FRESH AIR health interventions 19 -eg, communities' limited awareness of the harm of HAP exposure required us to deliver an extensive awareness programme 48 before the cleaner cooking programme 49 was implemented. This awareness programme emphasised the risks of HAP to children, which we had learned was a trigger to change behaviour.…”
Section: Discussionmentioning
confidence: 96%
“…Our study findings were translated directly into practical leverage points in the implementation strategies of FRESH AIR health interventions 19 -eg, communities' limited awareness of the harm of HAP exposure required us to deliver an extensive awareness programme 48 before the cleaner cooking programme 49 was implemented. This awareness programme emphasised the risks of HAP to children, which we had learned was a trigger to change behaviour.…”
Section: Discussionmentioning
confidence: 96%
“… 20 Biomass fuel is affordable, widely available, and awareness about chronic respiratory diseases and the risks of biomass fuel smoke is low. 21 Exacerbations were associated with high cost. Also, previous studies have reported that the more exacerbations, the higher the annual cost per COPD patient.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we stress the need for appropriate and systematic implementation and scale-up of these interventions. 21 , 31 , 35 , 37 All these implementations are likely to positively impact on the economic burden from CRDs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Lastly, an awareness gap was observed, since less than half of participants knew that burning biomass inside the household may be harmful health (48.5%). Similarly low levels of HAP awareness have been documented in other low-resource settings too (201).…”
Section: Summary Of Findingsmentioning
confidence: 71%
“…All thesis activities were implemented in times of an economic recession which has significantly impacted the size, structure and quality of healthcare services in Greece, with particular evidence capturing these unfavourable effects on patients' health (64,68,225). PHC is the most sustainable, accessible, equitable and cost-effective setting to tackle respiratory and other non-communicable diseases according to the WHO (201,226). The findings of this thesis speak to the need to work with policymakers to advocate for integration of PHC, the provision of universal coverage and the investigation potential synergies with existing services to offer high-quality and affordable respiratory care for all.…”
Section: Implications For Research Implementation Policy and Practicementioning
confidence: 99%